The translational inhibitor 4EBP/Thor is required for Drosophila adaptation to hypoxia - Sorianello, Eleonora Mariana (2025)
Adaptation to hypoxia requires the activation of concerted cellular mechanisms mainly dependent on the transcription factor HIF/Sima. 4E-BP/Thor is a CAP-dependent translation inhibitor involved in several cellular and developmental processes, which has been previously shown to be required for adaptation to starvation and oxidative stress. In this work, we show that 4E-BP/Thor is transcriptionally induced in Drosophila upon exposure to hypoxia in a Sima- and Foxo-dependent manner, and that loss of function of 4E-BP/Thor compromises fly survival in hypoxia. In Thor loss-of-function flies, alterations of mitochondria in the indirect flight muscle occur, and reactive oxygen species (ROS) accumulate, leading to premature lethality in hypoxia. These results highlight the importance of the translational regulator Thor in fly adaptation to hypoxia, presumably by contributing to maintain normal mitochondrial function, and preventing ROS accumulation in low oxygen conditions.